ANALISIS PENGELOLAAN DANA DESA DI DESA LUMU KECAMATAN BUDONG-BUDONG KABUPATEN MAMUJU TENGAH - Azlina, Nur; Rijal, Abdul; Hamzah, Hajrah (Jurnal Sosial Humaniora Sigli, 2024)
This study aims: to analyze the management of village fund in Lumu Village, Budong-Budong District, Central Mamuju Regency. The variable for this research is the management of village fund allocation which is measured using indicators contained in Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management. The subjects of this research are all village fund management reports and documents and apparatus that support the financial management process of village funds in Lumu Village, Budon-Budong District, Central Mamuju Regency. The focus of this research is the village fund management report and supporting documents, namely 2022, which is the village fund management process and village officials related to village fund management in Lumu Village, Budong-Budong District, Central Mamuju Regency. The village officials referred to are the Village Head, Village Secretary, Village Treasurer and Chairman of the BPD. Data collection techniques were carried out using documentation and interviews. Data analysis was carried out using qualitative descriptive analysis methods. The results of this research indicate that the management of village fund allocation in Lumu Village, Budong-Budong District, Central Mamuju Regency is quite appropriate at the planning and accountability stages, and less appropriate at the implementation and administration stages, while the reporting stages are not appropriate. Overall, the stages of many implementations that are lacking or even have not implemented the minister of home affairs Regulation Number 20 of 2018 at all.